Literasi Dakwah Mahasiswa Fakultas Dakwah dan Ilmu Komunikasi UIN Syahada Padangsidimpuan Melalui Media Sosial - Mhd. Latip kahpi; Ahmad Riski Sulaiman Nasution (IAIN Padangsidimpuan, 2025)
AbstractThis study aims to examine the increase in da'wah literacy of students at the Faculty of Da'wah and Communication Sciences (FDIK) UIN Syahada Padangsidimpuan in utilizing social media as a means of spreading Islamic messages in the digital era. The background of this study is based on the phenomenon of increasing da'wah activities on digital platforms such as Instagram, TikTok, and YouTube, which are carried out by students independently but have not been scientifically documented. The method used is descriptive qualitative with data collection techniques through in-depth interviews, observation of digital activities, and documentation of students' da'wah content. The results of the study show that students have experienced positive developments in terms of da'wah literacy, both in terms of understanding moderate and contextual da'wah messages, technical skills in content production, and digital communication strategies. Although still facing obstacles such as limited access to training and institutional support, students show high initiative in learning independently and building a digital da'wah community. This study concludes that social media is not only a tool for spreading da'wah, but also a collaborative learning space that encourages students to develop da'wah that is more relevant, creative, and adaptive to the needs of the digital community. Recommendations were given to the faculty to strengthen curriculum support, digital preaching training, and the development of media laboratories as a form of response to the dynamics of preaching inKeywords: Da'wah Literacy, Social Media, Digital Communication Abstrak Penelitian ini bertujuan untuk mengkaji peningkatan literasi dakwah mahasiswa Fakultas Dakwah dan Ilmu Komunikasi (FDIK) UIN Syahada Padangsidimpuan dalam memanfaatkan media sosial sebagai sarana penyebaran pesan keislaman di era digital. Latar belakang penelitian ini berangkat dari fenomena meningkatnya aktivitas dakwah di platform digital seperti Instagram, TikTok, dan YouTube, yang dilakukan oleh mahasiswa secara mandiri namun belum terdokumentasi secara ilmiah. Metode yang digunakan adalah kualitatif deskriptif dengan teknik pengumpulan data melalui wawancara mendalam, observasi aktivitas digital, dan dokumentasi konten dakwah mahasiswa. Hasil penelitian menunjukkan bahwa mahasiswa mengalami perkembangan positif dalam hal literasi dakwah, baik dari sisi pemahaman terhadap pesan dakwah yang moderat dan kontekstual, kemampuan teknis dalam produksi konten, maupun strategi komunikasi digital. Meskipun masih menghadapi kendala seperti keterbatasan akses pelatihan dan dukungan institusional, mahasiswa menunjukkan inisiatif tinggi dalam belajar secara mandiri dan membangun komunitas dakwah digital. Penelitian ini menyimpulkan bahwa media sosial tidak hanya menjadi alat penyebaran dakwah, tetapi juga ruang belajar kolaboratif yang mendorong mahasiswa untuk mengembangkan dakwah yang lebih relevan, kreatif, dan adaptif terhadap kebutuhan masyarakat digital. Rekomendasi diberikan kepada pihak fakultas untuk memperkuat dukungan kurikulum, pelatihan dakwah digital, dan pengembangan laboratorium media sebagai bentuk respons terhadap dinamika dakwah di era 4.0.